2011
DOI: 10.1590/s0034-89102011005000037
|View full text |Cite
|
Sign up to set email alerts
|

Infestación por triatominos en comunidades indígenas de Valledupar, Colombia

Abstract: RESULTS:Rhodnius prolixus showed a density index of 154.7%, for Triatoma dimidiata was 102.45%, T. maculata 109.25% and Panstrogylus geniculatus 0.3%. The mean infestation index was 40.54%, and mean Trypanosoma infection index was 9.4%. Of fi ve hemocultures positive for T. cruzi, three were enzimatically identifi ed as T. cruzi group I. Biopsies revealed few pathologic characteristics of infective process with these strains isolated from domiciliary triatomine bugs. CONCLUSIONS:The high triatomine infestation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 17 publications
0
14
0
2
Order By: Relevance
“…In this regard, this study provides the following evidence that highlights the epidemiological importance of this vector: (i) household-invading behavior in 12.8% of houses in the Mompos rural area and 6.8% in Talaigua Nuevo, (ii) higher seroprevalence and transmission in children under 15 years of age in areas with household-invading behavior (the Mompos rural area and Talaigua Nuevo), (iii) peridomiciliary infestation greater than 10% and (iv) a positive correlation between the presence of this species in houses with human seropositivity. Additionally, we previously reported a T. cruzi infection level of 57.1% of T. maculata [21], coupled with recent reports of infection of this species in the Caribbean lowlands [38], which supports the need to include T. maculata as a priority species in Chagas disease national vector control programs . …”
Section: Discussionmentioning
confidence: 64%
“…In this regard, this study provides the following evidence that highlights the epidemiological importance of this vector: (i) household-invading behavior in 12.8% of houses in the Mompos rural area and 6.8% in Talaigua Nuevo, (ii) higher seroprevalence and transmission in children under 15 years of age in areas with household-invading behavior (the Mompos rural area and Talaigua Nuevo), (iii) peridomiciliary infestation greater than 10% and (iv) a positive correlation between the presence of this species in houses with human seropositivity. Additionally, we previously reported a T. cruzi infection level of 57.1% of T. maculata [21], coupled with recent reports of infection of this species in the Caribbean lowlands [38], which supports the need to include T. maculata as a priority species in Chagas disease national vector control programs . …”
Section: Discussionmentioning
confidence: 64%
“…The present work provides new evidence supporting this argument. (i) We show the highest reported infection levels of household-invading T. maculata in Colombia, Venezuela and Brazil [5, 7, 9, 14, 16, 43]. (ii) The feeding patterns indicate that T. maculata is a generalist species with the ability to feed on different hosts, including humans.…”
Section: Discussionmentioning
confidence: 83%
“…Among them, T. maculata, was often considered to be of little epidemiological relevance due to its low infection rates and apparently ornithophilic preferences [5, 7, 9]. However, recent studies in the Colombian Caribbean region reported the occurrence of active transmission, and infection risk was associated with highly infected T. maculata in peridomestic human dwellings [6, 10, 14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…To apply the HRM technique to triatomines from the field, a total of 20 insects were collected in four localities of Colombia's Caribbean region, which display different eco-epidemiological transmission cycles of T. cruzi , as follows: (1) six domiciliary R. prolixus and three peridomiciliary T. dimidiata were collected by timed manual capture in an indigenous community with high epidemiological risk from the Sierra Nevada de Santa Marta area [41]; (2) three peridomiciliary T. maculata and one sylvatic Eratyrus cuspidatus (light-trap captured) were collected in the town of Talaigua Nuevo, located in the Bolivar department where a moderate epidemiological risk exists [42]; (3) three sylvatic T. dimidiata were collected manually in a hole in a fallen tree in Turbo, near the border between Colombia and Panama in the Antioquia department; this region is considered a nonendemic zone and a few reports on triatomine visiting houses have been released [43]; (4) finally, four sylvatic R. pallescens were collected in a palm tree in Aguachica in the Cesar department, where nondomiciliary triatomines have been reported [43]; they were caught using live chicken-bait traps (Table S1). …”
Section: Methodsmentioning
confidence: 99%